Talk : Application of Counseling in Mental Health Setting - Jabatan, Kaunseling; Fakulti Sains Kognitif dan, Pembangunan Manusia (2012)
Objective: to give exposure to participants related to the application of counseling in diverse mental health setting (sharing session) with the expert Prof Dr. Carl Jylland-Halverson from USA. Participants: academic staff and community including teachers, counselors, doctors, & practitioners in helping profession around Kota Samarahan and Kuching .